Postharvest physiology and effects of modified atmosphere packaging and anti-browning treatment on quality of pomegranate arils and aril-sac (CV. Bhagwa) - Aindongo, Wilhelmina Vulikeni (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScFoodSc)--Stellenbosch University, 2014.